Pulmonary benign metastasizing leiomyoma: A case report. (2018) - Khan, Malik; Faisal, Annum; Ibrahim, Hussain; Barnes, Terrance; VanOtteren, Glenn M.
Abstract: Uterine leiomyoma is the most common benign gynecological tumor. Rarely, it has benign extra-uterine growth patterns, including benign metastasizing leiomyoma (BML), with lungs being the most common metastatic site. We present a case of a 47-year-old female who, 3 years prior to presentation, underwent abdominal supra-cervical hysterectomy for benign leiomyoma. Approximately 6 months prior to presentation, she was seen for shortness of breath and chest pain. A CT of the chest revealed multiple new non-calcified pulmonary nodules bilaterally. PET/CT demonstrated mild FDG uptake in multiple lung nodules, with no significant extra-thoracic sites of abnormal FDG uptake. A CT guided lung biopsy showed a low grade, smooth muscle tumor. Immunohistochemical staining was positive for smooth-muscle actin and desmin, estrogen and progesterone receptor and was negative for CD117, HMB-45, CD34, pan cytokeratin and EMA. She underwent wedge resection of one of the nodules which confirmed the above findings. A cytogenetic analysis was also performed, which was consistent with pulmonary BML. She ultimately underwent left lower lobe resection and was started on a daily aromatase inhibitor. BML is a rare disease usually seen in women of reproductive age. The pathogenesis and treatment remain controversial. BML mostly tends to have an indolent course and a favorable outcome.